The Influence of Filler Loading and Alkaline Treatment on the Mechanical Properties of Palm Kernel Cake Filler Reinforced Epoxy Composites - Cionita, Tezara; Januar, Parlaungan Siregar; Wong, Ling Shing; Cheng, Wan Hee; Deni Fajar, Fitriyana; Jamiluddin, Jaafar; Ramli, Junid; Agustinus, Purna Irawan; Agung, Efriyo Hadi (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The manufacturing of materials, in conjunction with green technology, emphasises the need to employ renewable resources to ensure long-term sustainability. Re-exploring renewable elements that can be employed as reinforcing materials in polymer composites has been a major endeavour. The research goal is to determine how well palm kernel cake filler (PKCF) performs in reinforced epoxy composites. In this study, PKCF with 100 mesh was mixed with epoxy resin (ER) in various ratios ranging from 10% to 40% by weight. Hand lay-up with an open mould is proposed as a method for fabricating the specimen test. Surface modification of PKCF with varying concentrations of NaOH (5 wt.% and 10 wt.%) will be contrasted with the untreated samples. Using Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC), the effect of alkaline treatment will be examined. The tensile and maximum flexural strength of the untreated PKCF/ER composite were determined in this work, with a 30 wt.% of PKCF having the highest tensile strength of 31.20 MPa and the highest flexural strength of 39.70 MPa. The tensile and flexural strength were reduced to 22.90 MPa and 30.50 MPa, respectively, when the filler loading was raised to 40 wt.%. A 5 wt.% alkali treatment for 1 h improved the composites’ mechanical characteristics. Lastly, an alkali treatment can aid in the resolution of the problem of inadequate matrix and filler interaction. Alkaline treatment is a popular and effective method for reducing the hydroxyl group in fillers and, thus, improving interfacial bonding. Overall, palm kernel cake is a promising material used as a filler in polymer composites.